Environmental Impact of the Construction and Use of a House: Assessment of Building Materials and Electricity End-Uses in a Residential Area of the Province of Norte de Santander, Colombia - Castells, Francesc (2012)
The objective of this research is to assess the environmental impacts associated with the construction and use of a residential house. Building materials and electricity end-uses were as sessed. The study was used to high light some initiatives for the residential-building industrial sector and also some of the aspects that should be considered when trying to improve sustainability indicators. As a study case, a Colombian dwelling located in the city of Pamplona was chosen. The findings of this research showed that the highest environmental impacts during the dwelling’s life cycle take place during the operation phase of the dwelling, while construction phase generates about 7-28% of the impact. Transportation and maintenance combined account for less than 10% of the life cycle impacts.